Touching Wounds and Surfacing Wounds - Nina Panggabean (Sekolah Tinggi Theologia Nazarene Indonesia, 2023)
As a form of a traumatic event, childhood sexual abuse has deprived survivors of consciousness so that survivors weren’t willing to seek, pay attention to, and engage in recovery. However, the survivor’s consciousness could be regained. The question needed to be answered in this article is what kind of approach, psychologically and theologically, can the church, as their caregiver, use to regain survivors’ consciousness? This article will answer this question from the psychological perspective of Judith Herman on childhood sexual abuse and from the theological perspective of Shelly Rambo on “wounds” of posttraumatic events. At the end of this article, I propose a theopoetic-based approach to testimony as a basis for the church to approach survivors of childhood sexual abuse, such as approaching survivors, being open to witnessing the various wounds, responding to survivors’ testimonies, and engaging in the further discussions about the survivor’s reality through the ministry of the Word. This approach opens up possibilities for building a recovery process.